Study of virulence factors of Aeromonas hydrophila isolates causing acute abdominal dropsy and ulcerative diseases in Indian major carps - Shome, Rajeshwari; Shome, B R; Ram, Nagesh (Indian Journal of Fisheries, 2011)
Six Aeromonas hydrophila isolates from acute abdominal dropsy and ulcerative disease cases were evaluated for their virulence determinants. Morphological and biochemical characters’ similarity index, ranged from 0.866- 0.978 in relation to the first isolated A. hydrophila (3/95) when 46 parameters were considered. Similarity index for virulence determinants varied from 0.576-0.846 in similar comparisons taking proteolytic enzymes, amylase, cytotoxicity, dermonecrotic factor, haemagglutination and hemolysis into consideration. Generally, the haemagglutination of fish and chicken RBC appeared closely related to virulence in our isolates. Protease activity and their thermostability in extracellular preparation in highly virulent and weakly virulent strains were not significantly different. However, presence of either thermostable or thermolabile or both types of metalloprotease and serineprotease seem to be related to virulent strains, but none reflect the actual virulence. Mannose sensitive and resistant haemagglutination pattern indicates that a common mechanism does not exist for agglutination of different species and highly virulent isolates appear to possess different strategies for adherence and colonization. Western blot analysis showed that all the isolates shared atleast one common immunogen of 52 KD. However, its significance in relation to virulence has not been fully established.